Astrolabes in Medieval cultures - Rodríguez Arribas, Josefina; Burnett, Charles (Charles S. F.); Ackermann, Silke; Szpiech, Ryan (Brill, 2019)
First published as a special issue of the journal Medieval Encounters (vol. 23, 2017), this volume, edited by Josefina Rodríguez-Arribas, Charles Burnett, Silke Ackermann, and Ryan Szpiech, brings together fifteen studies on various aspects of the astrolabe in medieval cultures. The astrolabe, developed in antiquity and elaborated throughout the Middle Ages, was used for calculation, teaching, and observation, and also served astrological and medical purposes. It was the most popular and prestigious of the mathematical instruments, and was found equally among practitioners of various sciences and arts as among princes in royal courts. By considering sources and instruments from Muslim, Christian, and Jewish contexts, this volume provides state-of-the-art research on the history and use of the astrolabe throughout the Middle Ages. Contributors are Silke Ackermann, Emilia Calvo, John Davis, Laura Fernández Fernández, Miquel Forcada, Azucena Hernández, David A. King, Taro Mimura, Günther Oestmann, Josefina Rodríguez-Arribas, Sreeramula Rajeswara Sarma, Petra G. Schmidl, Giorgio Strano, Flora Vafea, and Johannes Thomann.